Confusions across the hemispheres: Taxonomic re-evaluation of two lanternshark species, Etmopterus lucifer and E. molleri (Squaliformes: Etmopteridae) - Shing-Lai Ng; Nicolas Straube; Kwang-Ming Liu; Shoou-Jeng Joung (Vertebrate Zoology)
Abstract The shark genus Etmopterus is the most species-rich shark genus, however, several of its species level taxa pose taxonomic challenges. Especially the Etmopterus lucifer species group is in need of a taxonomic re-evaluation. In the present study, we review the status of E. lucifer and E. molleri from the north- and southwestern Pacific applying an integrative taxonomic approach. Our dataset comprises 100 morphological characters and the mitochondrial NADH2 marker (1,010 bp) for 178 and 83 specimens, respectively. Our results show that E. lucifer and E. molleri from the Northwestern Pacific are distinct from specimens sampled in the Southwestern Pacific. We therefore (1) resurrect E. abernethyi for specimens in the southwestern Pacific hitherto assigned to E. lucifer, (2) synonymize the Northwestern Pacific E. burgessi with E. lucifer and (3) resurrect E. schmidti for specimens in the Northwestern Pacific hitherto assigned to E. molleri. A lectotype is designated herein for E. lucifer. Redescriptions of the four valid species, E. abernethyi, E. lucifer, E. molleri, and E. schmidti, are given and an updated key to all members of the E. lucifer group from the central Indo-Pacific is provided. The current division of the E. lucifer subgroups is challenged, as the key character, the relative length of flank-marking branches, shows great intraspecific variation.